آليات إستغلال الأملاك الوقفية العمرانية في التشريع الجزائري - غرياني, محمد العيد (My University, 2021)
يتناول هذا البحث طرق إستغلال الأملاك الوقفية المبنية والقابلة للبناء إضافة إلى الأرضي الوقفية المعرضة للخراب والاندثار، من خلال التعرض إلى مختلف الآليات والقوانين التشريعية والتنظيمية التي تنظم وتسير الأملاك الوقفية في التشريع الجزائري. - ويهدف هذا البحث إلى تسليط الضوء على مجموعة القوانين التي وضعها المشرع الجزائري وتحليلها ومعرفة الثغرات التي وقع بها. مما يستدعي إلى ضرورة الإهتمام بالوقف لإعادة دوره الإجتماعي والإقتصادي ليحقق ما هو مطلوب منه , وبعد عرضنا لطرق إستغلال الاملاك الوقفية والتي سعى المشرع الجزائري جاهدا من خلال إستحداث مجموعة من العقود إلى ضبط تسييرها وأحكامها , إلا أن تلك الجهود التي بذلها المشرع لم توفق إلى حد ما بسبب صعوبة الحصر الكامل للأوقاف وتسجيلها وكذا بسبب العديد من التجاوزات الت تعترض الأملاك الوقفية , مما يستدعي الإهتمام أكثر بالممتلكات الوقفية . This research deals with the ways of exploiting the built and buildable endowment properties in addition to the endowment lands that are subject to destruction and extinction, through exposure to the various mechanisms and legislative and regulatory laws that regulate and operate the endowment properties in the Algerian legislation. - This research aims to shed light on the set of laws developed by the Algerian legislator, analyze them, and find out the loopholes in which he fell. Which calls for the need to pay attention to the endowment to restore its social and economic role to achieve what is required of it, and after we presented the ways of exploiting the endowment properties, which the Algerian legislator strived through Introducing a set of contracts to control its management and provisions, but these efforts made by the legislator did not succeed to some extent due to the difficulty of fully enumerating and registering endowments, as well as because of the many abuses that affect endowment properties, which calls for more attention to endowment properties.
قانون عقاري
Keywords: آليات الإستغلال - الأملاك الوقفية العمرانية - التشريع الجزائري; Exploitation mechanisms - urban endowment properties - Algerian legislation